Effects of Steel Fiber and Compaction Process on the Flexural Strength of Reinforced Concrete Beams with Longitudinal Cold Joints - Maysaa Aziz Mahdi; Ali Abd Sultan (Zien Journals, 2023)
Due to many reasons, concrete may not be poured in a single connected operation and therefore joints are formed in locations of old-new concreting. This study discusses the behavior of Reinforced Concrete (RC) and Fiber Reinforced Concrete (FRC) beams containing longitudinal cold joints under two compaction scenarios. The first layer in the first scenario is compacted prior pouring of the second layer, while the other scenario investigates the effects of leaving the first layer uncompacted. It is believed the compaction of the first layer has an important effect on the bonding characteristics between both concrete layers as it may affect the roughness of the joint interface. The study also investigates the time elapsed before pouring of the second layer. The cold joint was located at compression fiber at 0.7h from bottom. Under the four-point load testing, ten 100×160×1000 mm RC beams have been tested and evaluated. Three groups of beams were separated from one another. Four beams make up the first group; one uses as a control, while the other three have horizontal cold joints, the second group consists of three beams with horizontal cold joint and without compacted first layer. whereas the third group consists of three beams with horizontal cold joint adding steel fiber to strengthen the samples that have the least load. The results showed a decrease in ultimate load, ductility and energy absorption capacities for specimen B1.5-RC-NC, B3.0-RC-NC and B4.5-RC-NC, ultimate load, ductility and energy absorption capacities were decreased (9.03%,50.5%,50.9%), (23.4%,31.5%,33.3%) and (27.7%,84.0%, 85.6%) respectively in comparison with control beam. While the decrease in ultimate load, ductility, energy absorption capacities for specimen with steel fiber B1.5-FRC-NC, B3.0-FRC-NCand B4.5-FRC-NC were (5.02%,37.0%, 38.3%), (19.2%,21.1%,21.6%) and (26.5%,58.4%, 58.5)
Keywords: Cold joint; steel fiber; flexural strength